THE EFFECT OF PICTURE CARD GAMES TO STUDENTS OF ELEMENTARY SCHOOL’S VOCABULARY MASTERY - Riky Oktavianus Depari; Azwandi Azwandi; Syahrial Syahrial (Universitas Bengkulu, 2017)
The aim of this study was to investigate the effect of picture card games technique toward students’ vocabulary mastery. The participant was all the fifth year students of SD N 99 Kota Bengkulu that consisted of 68 students, the students divided into two classes, namely class VA and VB. The sample were the two classes which 34 students in each class. The students were divided into two groups, the experimental and the control groups. The experimental group received treatment by using card games techniques, while the control group was taught by using conventional technique. The pre-test was given to the two groups before giving the treatment. It found that there was no significant between the two groups in vocabulary mastery before giving the treatment. However, after giving the treatment, post-test was given and it found that there was a significant difference between the two groups. It can be concluded that card games technique gave positive effect toward the students’ English vocabulary mastery of SD N 99 Kota Bengkulu.